The World Health Organization's Actions Within the United Nations System to Facilitate a Whole-of-Society Response to COVID-19 at Country Level - Samaan, Gina; McPherson, Michelle; Eidman, Johan; Obubah, Offeibea; Baptiste, Jean-Pierre; Kuppens, Lianne; Von Harbou, Kai; Sembiring, Miftahul Fahmi; Acharya, Shambhu; Graaff, Peter (Frontiers in Public Health, 2022)
The COVID-19 pandemic highlighted that managing health emergencies requires more than an effective health response, but that operationalizing a whole-of-society approach is challenging. The World Health Organization (WHO), as the lead agency for health within the United Nations (UN), led the UN response at the global level through the Crisis Management Team, and at the country level through the UN Country Teams in accordance with its mandate. Three cases studies – Mali, Cox’s Bazar in Bangladesh and Uzbekistan – provide examples of how WHO contributed to the whole-of-society response for COVID-19 at the country level. Interviews with WHO staff, supplemented by internal and external published reports, highlighted that the action of WHO comprised technical expertise to ensure an effective whole-of-society response and to minimize social disruption, including those affecting peacekeeping in Mali, livelihood sectors in Cox’s Bazar and the education sector in Uzbekistan. Leveraging local level volunteers from various sectors led to both a stronger public health response and the continuation of other sectoral work. Risk communication and community engagement emerged as a key theme for UN engagement at country level. These collective efforts of operationalising whole-of-society response at the country level need to continue for the COVID-19 response, but also in preparedness for other health and non-health emergencies. Building resilience for future emergencies requires developing and exercising multi-sectoral preparedness plans and benefits from collective UN support to countries. COVID-19 had many impacts outside of health, and therefore emergency preparedness needs to occur outside of health too.